2021
DOI: 10.3892/etm.2021.10288
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus‑mediated transfer of gene encoding fibroblast growth factor‑18 inhibits intervertebral disc degeneration

Abstract: Fibroblast growth factor 18 (FGF-18) is a well-characterized anabolic growth factor involved in cartilage homeostasis. However, the effect of FGF-18 on intervertebral disc (IVD) degeneration has not been investigated. The present study aimed to investigate the role of FGF-18 in the process of rabbit IVD degeneration. In vitro, primary nucleus pulposus cells (NPs) were cultured and transfected with a lentivirus. Tert-butyl hydroperoxide (TBHP) was used to induce apoptosis in NPs on the second passage, while ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The synovitis we observed with rhFGF18 treatment was therefore attributed to the consistent disruption of the joint capsule due to repeated injections, which likely drove the pathology. These findings are in line with the previously published studies of viral vector–delivered rhFGF18 in the pinna and intravertebral disk, 41 , 60 which also did not report any treatment-related side effects.…”
Section: Discussionsupporting
confidence: 92%
“…The synovitis we observed with rhFGF18 treatment was therefore attributed to the consistent disruption of the joint capsule due to repeated injections, which likely drove the pathology. These findings are in line with the previously published studies of viral vector–delivered rhFGF18 in the pinna and intravertebral disk, 41 , 60 which also did not report any treatment-related side effects.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, FGF18 can inhibit the apoptosis of NP cells, thereby providing further protection for the IVD. FGF18 increases the expression of Col-2 and CA12 in NP cells while decreasing degeneration in vertebral joint NP [ 11 , 144 ]. Currently, research related to FGF18 primarily focuses on cartilage and NPs rather than other tissues like AF.…”
Section: Fgfs and Ivddmentioning
confidence: 99%
“…For example, FGF1 and FGF8 may contribute to cartilage destruction during the development of OA [ 9 , 10 ], whereas FGF18 can promote cartilage repair and protect joint cartilage integrity. Additionally, FGF18 inhibits apoptosis of nucleus pulposus (NP) cells protecting intervertebral discs (IVDs) affected by IVDD [ 11 ]. In cases of sarcopenia and OP, FGF shows potential for slowing down or reversing disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al ( Wu et al, 2014 ) reported that lentiviral vector-mediated gene expression lasted nearly twice as long as AAV in human NP cells. The regulation of IDD-related factors such as inflammation, ECM and apoptosis by lentiviral vectors has been reported ( Farhang et al, 2019 ; Lin et al, 2021 ; Lu et al, 2021 ; Lu and Lin, 2021 ).…”
Section: The Application Of Different Transmission Systemsmentioning
confidence: 99%